Dimensioning of a Wireless Power Transfer charger - Oumaima Benzouina; Hassan El Fadil; Abdellah Lassioui; El Jeilani Sidina (EPJ Web of Conferences, 2025)
A bidirectional and contactless charging system for electric vehicles (EVs) is described, leveraging energy transfer via inductive coupling (ICPT). The paper discusses the operational principles, system sizing, and design of both vehicle-side and grid-side boards, presenting a comprehensive solution for efficient EV charging infrastructure.